2011
DOI: 10.1366/11-06384
|View full text |Cite
|
Sign up to set email alerts
|

A Compact Diode Laser Cavity Ring-Down Spectrometer for Atmospheric Measurements of NO<SUB>3</SUB> and N<SUB>2</SUB>O<SUB>5</SUB> with Automated Zeroing and Calibration

Abstract: A compact rack-mounted cavity ring-down spectrometer (CRDS) for simultaneous measurements of the nocturnal nitrogen oxides NO(3) and N(2)O(5) in ambient air is described. The instrument uses a red diode laser to quantify mixing ratios of NO(3) (at its absorption maximum at 662 nm) and of N(2)O(5) following its thermal dissociation to NO(3) in a second detection channel. The spectrometer is equipped with an automated zeroing and calibration setup to determine effective NO(3) absorption cross-sections and NO(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…This gas stream was periodically added to the main inlet with the aid of a normally open two-way valve connected to a vacuum pump in a similar fashion as described earlier for N 2 O 5 and PAN (Tokarek et al, 2014;Odame-Ankrah and Osthoff, 2011 (Wieser and Berglund, 2009) and our previously observed ratios of 0.315 ± 0.003 in Calgary and 0.3065 ± 0.0002 in Pasadena (Mielke et al, 2013). The reason(s) for these differences is unclear but they may be a result of fractionation processes (Koehler and Wassenaar, 2010;Volpe et al, 1998), a topic outside the scope of this paper.…”
Section: Quantification Of Clno 2 By Iodide Chemical Ionization Mass mentioning
confidence: 99%
See 2 more Smart Citations
“…This gas stream was periodically added to the main inlet with the aid of a normally open two-way valve connected to a vacuum pump in a similar fashion as described earlier for N 2 O 5 and PAN (Tokarek et al, 2014;Odame-Ankrah and Osthoff, 2011 (Wieser and Berglund, 2009) and our previously observed ratios of 0.315 ± 0.003 in Calgary and 0.3065 ± 0.0002 in Pasadena (Mielke et al, 2013). The reason(s) for these differences is unclear but they may be a result of fractionation processes (Koehler and Wassenaar, 2010;Volpe et al, 1998), a topic outside the scope of this paper.…”
Section: Quantification Of Clno 2 By Iodide Chemical Ionization Mass mentioning
confidence: 99%
“…Further, the collisional dissociation chamber (CDC) was operated in declustering mode (−22.7 V) to break up ion clusters. Calibrations and matrix effect correction procedures and a time series of the PAN and PPN data were presented by Tokarek et al (2014 The CRDS used in this work was an amalgamated version of two instruments described earlier (Paul and Osthoff, 2010;Odame-Ankrah and Osthoff, 2011), called Improved Detection Instrument for Nitrogen Oxide Species (iDinos) (Odame-Ankrah, 2015). A schematic of the optical layout is shown in Fig.…”
Section: Quantification Of Clno 2 By Iodide Chemical Ionization Mass mentioning
confidence: 99%
See 1 more Smart Citation
“…The residence time prior 130 to the ethane addition point (~2.0 s) suffices to destroy ROx radicals (via reaction with NO) prior to chemical amplification. Addition of either NO or ethane is on/off modulated using 2-way normally-open valves connected to a pump via 50 μm critical orifices (Lenox Laser, Glen Arm, MD) in a similar fashion as described earlier (Odame-Ankrah and Osthoff, 2011).…”
Section: Dual-channel Td-perca-crds 125mentioning
confidence: 99%
“…Nitrate radical oxidation can lead to significant amounts of SOA on global and regional scales. Due to a lack of information on the identity and volatility of later-generation BVOC + NO 3 products, most models parameterize SOA formation separately from gas-phase chemistry using either the Odum two-product (Odum et al, 1996) fit, volatility basis set (VBS) fit, or fixed yield (Table 5). Based on the understanding of SOA pathways at the time, Hoyle et al (2007) found that up to 21 % of the global average SOA burden may be due to NO 3 oxidation, and Pye et al (2010) predicted ∼ 10 % of global SOA production was due to NO 3 .…”
Section: Influence On Organic Aerosolmentioning
confidence: 99%